2013
DOI: 10.1128/jvi.02782-12
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Function of an Epitope-Tagged p7 Viroporin in Hepatitis C Virus-Producing Cells

Abstract: The hepatitis C virus (HCV) viroporin p7 is crucial for production of infectious viral progeny. However, its role in the viral replication cycle remains incompletely understood, in part due to the poor availability of p7-specific antibodies. To circumvent this obstacle, we inserted two consecutive hemagglutinin (HA) epitope tags at its N terminus. HA-tagged p7 reduced peak virus titers ca. 10-fold and decreased kinetics of virus production compared to the wild-type virus. However, HA-tagged p7 rescued virus pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 70 publications
(149 reference statements)
7
57
1
Order By: Relevance
“…1B, compare lanes 1 and 3). These results confirmed the recent report by Vieyres and colleagues who showed that introducing an N-terminal double HA tag to the p7 of the gt2a/2a chimera Jc1 allowed the production of virus, albeit at a reduced level compared to that from Jc1 (42). Since p7 in HJ3-5 is derived from gt1a, these results also indicate that p7 with an N-terminal epitope tag was functional in virus production in both gt1a and gt2a genetic backgrounds.…”
Section: Resultssupporting
confidence: 81%
“…1B, compare lanes 1 and 3). These results confirmed the recent report by Vieyres and colleagues who showed that introducing an N-terminal double HA tag to the p7 of the gt2a/2a chimera Jc1 allowed the production of virus, albeit at a reduced level compared to that from Jc1 (42). Since p7 in HJ3-5 is derived from gt1a, these results also indicate that p7 with an N-terminal epitope tag was functional in virus production in both gt1a and gt2a genetic backgrounds.…”
Section: Resultssupporting
confidence: 81%
“…p7 has been shown by overexpression studies and in full-length HCV to predominantly localize to ER membranes (Carrère-Kremer et al, 2002;Haqshenas et al, 2007;Wozniak et al, 2010), including those associated with mitochondria (Griffin et al, 2005). Cell surface expression has also been noted (Carrère-Kremer et al, 2002) and recent studies of HA-tagged or native proteins in full-length virus have observed associations with HCV core, E2 and NS5A proteins (Bentham et al, 2013;Vieyres et al, 2013).…”
Section: Hcv P7mentioning
confidence: 99%
“…Viable full-length HCV containing IRES elements inserted between E2 and p7 or p7 and NS2 argued against a functional role for p7 precursors (Jones et al, 2007). Both early-and late-acting defects in virion production have been described where p7 was (partially) deleted, mutated at specific residues or treated with inhibitors (Bentham et al, 2013;Foster et al, 2011Foster et al, , 2014Jones et al, 2007;Steinmann et al, 2007a;Vieyres et al, 2013;Wozniak et al, 2010). This is now known to result from p7 performing multiple functions within infected cells, comprising distinct protein-protein interactions as well as its channel-forming activity.…”
Section: Hcv P7mentioning
confidence: 99%
“…These findings could give a functional rationale for previously published data. Furthermore, it was suggested that E2 and p7 might interact (9,44,45), and Gentzsch and colleagues postulated that the p7-RR/QQ mutant has a defect at the step of capsid envelopment. Strikingly, our data suggest that mutation of the dibasic motif in p7 selectively impairs the interaction with E2 (44).…”
Section: Hcv Protein Interactions Determined Via Facs-fret-tomentioning
confidence: 99%
“…Then immunofluorescence staining with specific antibodies was performed to detect areas of protein co-localization by means of confocal microscopy. We quantified co-localization using Costes Pearson's correlation (84) major functional impairments as a consequence of the tag (9,10,16,(23)(24)(25)(26)(27)(28)(29).…”
Section: Hcv Protein Interactions Determined Via Facs-fret-tomentioning
confidence: 99%